2020
DOI: 10.1002/agj2.20149
|View full text |Cite
|
Sign up to set email alerts
|

Winter cover crop production and water use in Southern Great Plains cotton

Abstract: Cover crops can provide several ecosystem services in agricultural cropping systems.Benefits may be enhanced with increasing cover crop biomass production. In waterlimited environments, feasibility of cover crop germination and production is not always certain. This study was conducted to determine differences in biomass production, water use, and water use efficiency (WUE) between monoculture cover crops and a mixture at Chillicothe, TX, in the Southern Great Plains under rainfed conditions in a continuous co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…Compared to NT without a cover crop, lint yields increased by 2.8% following a cover crop mix, 4.8% following peas, and 6.1% following vetch. As lint yields were not different following clover, DeLaune and Mubvumba (2020) reported that the clover cover crop had less biomass production and water use efficiency than the mix, peas, and vetch.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared to NT without a cover crop, lint yields increased by 2.8% following a cover crop mix, 4.8% following peas, and 6.1% following vetch. As lint yields were not different following clover, DeLaune and Mubvumba (2020) reported that the clover cover crop had less biomass production and water use efficiency than the mix, peas, and vetch.…”
Section: Resultsmentioning
confidence: 99%
“…Although recorded precipitation was greater in 2015, increased precipitation did not correlate to increased lint yields as cotton was planted late and adverse environmental conditions were endured during the growing season. Mean cover crop biomass production from 2012–2017 was 748, 1,562, 2,301, 2,480, and 2,863 kg ha –1 for clover, wheat, vetch, pea, and the mix, respectively (DeLaune & Mubvumba, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the extended duration of time between cover crop termination and the planting of the winter wheat cash crop were not the same as our study in which cover crops were immediately planted following cotton harvest. Although not quantified, the grass species of our cover crop mixture, rye, was dominant (DeLaune & Mubvumba, 2020). McDonald et al.…”
Section: Discussionmentioning
confidence: 99%
“…Two 0.42‐m 2 quadrats of cover crop herbage were then clipped at the 5 cm height from each of NT with cover crop treatments, weighed, and dried at 65°C for dry matter determination. Total C and N content was determined using combustion analysis using an Elementar Vario Max elemental analyzer (Elementar, Langenselbold, Germany; DeLaune & Mubvumba, 2020).…”
Section: Methodsmentioning
confidence: 99%